The role of meaning in life in community-dwelling older adults with depression and relationship to other risk factors - Volkert, Jana (Aging & mental health, 2019)
Objectives: The aims of this study were to examine the association of Meaning in Life (MiL) with sociodemographic and physical factors, and its association with depression in older people.Method: A cross-sectional survey with a sample of N = 2104 older adults from communities of four European countries was conducted, using an age-appropriate interview for the diagnosis of depression and the Schedule for Meaning in Life Evaluation (SMiLE) questionnaire to assess MiL.Results: Overall, MiL was particularly low in old male participants, in older people from Ferrara (Italy), those with a lower religious affiliation, fewer social contacts, and poorer physical health. Furthermore, younger old age (65-69 compared to 80-84 year olds), female gender, being married, living in Geneva and poorer physical health were significantly associated with a higher risk for depression. In addition, lower MiL significantly increased the likelihood to suffer from depression in older people. An interaction effect of study center and MiL also emerged: with decreasing MiL the risk for depression significantly increases in Hamburg compared to the other study centers.Conclusion: This study underlines the association of MiL and depression in old age. Integration of meaning-specific aspects in treatment for older adults with depression may be promising.